2015
DOI: 10.1128/aem.04144-14
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Engineering Improves Tolerance for Replacement Jet Fuels in Saccharomyces cerevisiae

Abstract: cMonoterpenes are liquid hydrocarbons with applications ranging from flavor and fragrance to replacement jet fuel. Their toxicity, however, presents a major challenge for microbial synthesis. Here we evolved limonene-tolerant Saccharomyces cerevisiae strains and sequenced six strains across the 200-generation evolutionary time course. Mutations were found in the tricalbin proteins Tcb2p and Tcb3p. Genomic reconstruction in the parent strain showed that truncation of a single protein (tTcb3p 1-989 ), but not it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Tolerance of S. cerevisiae toward limonene and other monoterpenes could be enhanced by expression of a fungal efflux pump that was demonstrated to be involved in monoterpene resistance of the bark beetle-associated pine tree pathogen Grosmannia clavigera (Wang et al 2013 ). Recently, evolutionary engineering of S. cerevisiae demonstrated a truncation of a tricalbin protein with a probable function in cell wall integrity regulation to confer a drastic improvement in tolerance toward limonene and other monoterpenes (Brennan et al 2015 ).…”
Section: Toxicity and Solvent Tolerancementioning
confidence: 99%
“…Tolerance of S. cerevisiae toward limonene and other monoterpenes could be enhanced by expression of a fungal efflux pump that was demonstrated to be involved in monoterpene resistance of the bark beetle-associated pine tree pathogen Grosmannia clavigera (Wang et al 2013 ). Recently, evolutionary engineering of S. cerevisiae demonstrated a truncation of a tricalbin protein with a probable function in cell wall integrity regulation to confer a drastic improvement in tolerance toward limonene and other monoterpenes (Brennan et al 2015 ).…”
Section: Toxicity and Solvent Tolerancementioning
confidence: 99%
“…Adaptive evolution has been proven to be effective in improving cellular tolerance against disadvantageous environments and the foundation is beneficial mutant genes [24]. Brennan et al [2] reported that Saccharomyces cerevisiae had a 4-fold increased tolerance toward the biojet fuel blend AMJ-700t because of one gene mutant (tTcb3p). The mutant E72 from Bacillus subtlis168 exhibited higher growth rate and xylose consumption rate with three mutations (araR, sinR, and comP) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive laboratory evolution was served as a genome-wide method for improving desirable phenotypes without the knowledge of genetic determinants for network information about those phenotypes [22][23]. And it was successfully employed to identify biological solutions to biofuel and alcohol toxicity in S. cerevisiae [24][25][26][27][28][29][30]. In this study, we used adaptive laboratory evolution to enhance yeast strain's tolerance toward higher glucose and isobutanol concentration in fermentation.…”
Section: Introductionmentioning
confidence: 99%